Circulating microRNAs as biomarkers in traumatic brain injury. (February 2019) - Toffolo, Kathryn; Osei, Jennifer; Kelly, William; Poulsen, Austin; Donahue, Kaitlynn; Wang, Jiefei; Hunter, Madison; Bard, Jonathan; Wang, Jianxin; Poulsen, David
Abstract: Preclinical and clinical studies can be greatly improved through the inclusion of diagnostic, prognostic, predictive or pharmacodynamics biomarkers. Circulating microRNAs (miRNAs) represent highly stable targets that respond to physiological and pathological changes. MicroRNA biomarkers can be detected by highly sensitive and absolutely quantitative methods currently available in most clinical laboratories. Here we review preclinical and clinical studies that have examined circulating miRNAs as potential diagnostic and prognostic biomarkers. We also present data that suggests pharmacodynamics biomarkers can be identified that are associated with neuroprotection in general. Although circulating miRNA can serve as useful tools, it is clear their expression profiles are highly sensitive to changing conditions and are influenced by a broad range of parameters including age, sex, body mass index, injury severity, time of collection, as well as methods of processing, purification and detection. Thus, considerable effort will be required to standardize methods and experimental design conditions before circulating miRNAs can prove useful in a heterologous injury like TBI. This article is part of the Special Issue entitled "Novel Treatments for Traumatic Brain Injury". Highlights: Changes in plasma miRNA levels can be readily detected following traumatic brain injury. Plasma miRNA levels can be altered by a variety factors including the methods used to purify and quantifying samples. Plasma miRNA changes can serve as pharmacodynamic biomarkers of treatment.